Kinetics of hydrogen desorption from Zircaloy-4: Experimental and modelling. (13th August 2019) - Juillet, C.; Tupin, M.; Martin, F.; Auzoux, Q.; Berthinier, C.; Miserque, F.; Gaudier, F.
Abstract: Under Pressurized Water Reactor normal operating conditions, the external surface of zirconium alloys cladding absorbs a fraction of the hydrogen produced by water reduction. During spent fuel transport, hydrogen may desorb from the cladding. The study aims to identify and quantify the rate-limiting step in the hydrogen desorption process initially present in the alloy. To better understand this process, the Thermal Desorption Spectrometry (TDS) was used in association with X-ray Photoelectron Spectroscopy analysis. TDS results were analysed with finite elements simulations using the Cast3M code. The optimization of the kinetic constants of hydrogen desorption was performed with CEA (Alternative Energies and Atomic Energy Commission)-tool URANIE. Results showed that hydrogen desorption kinetics from the metal is limited by the surface molecular recombination. Arrhenius-type temperature dependence of kinetic constants allowed to simulate experimental data with a good agreement. The optimized activation energy and the pre-exponential factor for desorption processes were in the range of 290 ± 10 kJ mol −1 and 3 × 10 7  m 4  mol −1  s −1 respectively. Highlights: Thermal desorption analysis identified the rate-limiting step of hydrogen desorption. The hydrogen desorption rate is controlled by the surface recombination step. By coupling Cast3M with URANIE, the surface recombination constant was quantified. The desorption rate constant equals: k d e s ' = 3 x 10 7 . exp ( − 2.90 x 10 5 R T ) m 4 mol −1 s −1 .